The Jawi Wetan Christian Church in the Muslim community: SDGs perspective - Lukito, Harjo (Sekolah Tinggi Manajemen IPMI, 2024)
This article examines the existence of the Jawi Wetan Mojokerto Christian Church in the Muslim community, not only the existence of its buildings and community, but its interaction and collaboration with the Muslim community in social activities which generally focus on the areas that are the main objectives of the Sustainable Development Goals. The religious life that is built is not just about tolerance, but spaces for harmony in social and humanitarian aspects have been created. Through qualitative research with descriptive presentation, case study analysis was used to reveal the social, economic and environmental impacts of this collaboration. The research object is GKJW Mojokerto, located in Sentanan Village, Kranggan District, Mojokerto City, which is less than 20 meters from the AL Muaishym Mosque. The four research sources are Koster GKJW Mojokerto, Chairman of the Mosque Takmir, a historian, former Bible teacher at GKJW Mojokerto, and the Sentantan Neighborhood RT Management. The concept and perspective of Sustainable Development Goals is the author's main focus in conducting the analysis. These findings lead to the conclusion that interfaith cooperation between Christians and Muslims is important in achieving the SDGs in Indonesia. Effective dialogue and collaboration in responding to crucial issues such as the environment, human rights and economic development. It is important to strengthen interfaith dialogue and cooperation efforts and establish sustainable dialogue forums to support the achievement of SDGs targets.